On the Credibility of Currency Boards - Switgard Feuerstein; Oliver Grimm (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2004)
The paper compares the credibility of currency boards and (standard) pegs. Abandoning a currency board requires a time-consuming legislative process and an abolition will thus be previously expected. Therefore, a currency board solves the time inconsistency problem of monetary policy. However, policy can react to unexpected shocks only with a time lag, thus the threat of large shocks makes the abolition more likely. Currency boards are more credible than standard pegs if the time inconsistency problem dominates. In contrast, standard pegs, that can be left at short notice, are more credible if exogenous shocks are highly volatile and constitute the dominant problem.
Keywords: F33; E52; E42; 330; monetary policy; currency board; standard peg; credibility; time inconsistency problem; stochastic purchasing power parity; Currency Board; Stufenflexibilität; Glaubwürdigkeit; Vergleich; Zeitkonsistenz; Schock; Kaufkraftparität; Theorie